ON THE ELABORATION OF THE LEGAL STATUS OF THE GRAND DUCHY OF FINLAND - M. A. Isaev (Московский журнал международного права, 2019)
INTRODUCTION. The article deals with the insufficiently explored in our legal science the law status of separate territories of the Russian Empire. As an example we took the most “liberal” status of the Grand Duchy of Finland. The Finnish elite had become more and more separate in its mood from one decade to another during the XIX century that lead to formation of state status theory of Finland and its special union connection with the Empire. This status was just simple like unions of Sweden and Norway, Austria and Hungary, England and Scotland. That was the main idea of this theory. MATERIALS AND METHODS. The material for the article was the legislation of the Russian Empire (Full Digest of the Laws of the Russian Empire) and Grand Duchy of Finland (Finlands lagar, Storfurstendömet Finlands Författnings-Samling). Another sources were the works of European and Russian doctors of law, especially the doctrine of international law, how it was worked out at the end of the XIX century. The works of Russian and Finnish historians were also the sources of this article. The methodological basis of this research consists of comparative law and juridical-dogmatic methods. As the main basic method was taken analytical method (deductive and inductive methods of research). RESEARCH RESULTS. In the article the author shows the complicated political reasons that induced Russia to annex Finland and to settle very liberal and privileged ruling regime in Finland. This complicated complex of reasons that had geopolitical, economic, cultural and legal roots permitted to establish a unique status of Finland – from one point of view; but promoted so-called fennomans to demand a separate status for Finland as an independent state – from another point of view. This intention was supported by the western science of international law (first of all in Germany and Sweden) but at the same time it had challenged the annihilating criticism of the Russian lawyers. DISCUSSION AND CONCLUSIONS. As the result of the discussion and the next actions of the Imperial government the theory of the separate Finland was destroyed. But the crush of the Russian historical power in February 1917 and the coup d’etat that was made by bolsheviks the Finnish separatists could solve their problems. The obtaining of independence by Finland in December 1917 had the most destroying consequences in the XX century: two wars of 1939–1940; 1941–1944 and the growth of russofobia in recent Finland.